Chemoimmunotherapy with inotuzumab ozogamicin combined with mini‐hyper‐CVD, with or without blinatumomab, is highly effective in patients with Philadelphia chromosome–negative acute lymphoblastic leukemia in first salvage. Issue 20 (11th October 2018) - Jabbour, Elias; Sasaki, Koji; Ravandi, Farhad; Huang, Xuelin; Short, Nicholas J.; Khouri, Maria; Kebriaei, Partow; Burger, Jan; Khoury, Joseph; Jorgensen, Jeffrey; Jain, Nitin; Konopleva, Marina; et al.
Abstract : Background: The outcomes of patients with relapsed or refractory (R‐R) acute lymphoblastic leukemia (ALL) are poor. Inotuzumab ozogamicin and blinatumomab have single‐agent activity in R‐R ALL. Their addition to low‐intensity chemotherapy may further improve the outcomes of patients with ALL in their first relapse. Methods: The chemotherapy was lower in intensity than conventional hyperfractionated cyclophosphamide, vincristine, adriamycin, and dexamethasone and was called mini‐hyperfractionated cyclophosphamide, vincristine, and dexamethasone (or mini‐HCVD). Inotuzumab was given on day 3 of each of the first 4 cycles at 1.8 to 1.3 mg/m 2 for cycle 1, and this was followed by 1.3 to 1.0 mg/m 2 for subsequent cycles. From patient 39 onward, the inotuzumab dose was reduced and fractionated into weekly doses (0.6 and 0.3 mg/m 2 during cycle 1 and 0.3 and 0.3 mg/m 2 during subsequent cycles), and blinatumomab was administered for up to 4 cycles after inotuzumab therapy. Results: Forty‐eight patients with Philadelphia chromosome–negative ALL with a median age of 39 years were treated during their first relapse. Overall, 44 patients (92%) responded, with 35 of them (73%) achieving a complete response. The overall minimal residual disease negativity rate among the responders was 93%. Twenty‐four patients (50%) underwent allogeneic stem cell transplantation (ASCT). Veno‐occlusive disease of any grade occurred in 5 patients (10%). With a median follow‐up of 31 months, the median progression‐free survival (PFS) and the median overall survival (OS) were 11 and 25 months, respectively. The 2‐year PFS and OS rates were 42% and 54%, respectively. Of the 24 patients (50%) who underwent ASCT, 14 patients were alive at the last follow‐up (13 [54%] in remission). Of the remaining 20 responding patients who did not undergo subsequent ASCT, 6 (30%) remained in remission at the last follow‐up. According to propensity score matching, the combination of mini‐HCVD and inotuzumab with or without blinatumomab conferred better outcomes than intensive salvage chemotherapy or inotuzumab alone. Conclusions: The combination of inotuzumab and low‐intensity mini‐HCVD chemotherapy with or without blinatumomab shows encouraging results in patients with ALL in first salvage. Abstract : The immunochemotherapy combination of inotuzumab and mini‐hyper‐CVD with or without blinatumomab is safe and effective in patients with acute lymphoblastic leukemia in fi rst salvage. New strategies, including a weekly schedule of lower doses of inotuzumab, the sequential use of blinatumomab, and the selection of the least hepatotoxic transplant preparative regimens, may further improve outcomes.